Visually Enhanced Lesion Scope - Novel Chair Side Diagnostic Tool for Potentially Malignant Disorders - A Meta Analysis - Deepa Ponnaiyan; C L Krithika (International Journal of Pharma and Bio Sciences, 2021)
Oral cancer screening is pivotal as early diagnosis can dramatically increase the survival rate. Visually Enhanced Lesion Scope (VELscope) is a handheld device that uses natural tissue fluorescence to visualize the abnormalities of the oral mucosa that are not apparent with naked eyes. The objective was to assess the sensitivity and specificity of VELscope in screening for dysplasia, potentially malignant disorders and oral cancer. Three electronic databases were used to obtain the literature with desired criteria. A Meta – Analysis to evaluate the effectiveness of VELscope was undertaken. The data collected was statistically analyzed and Meta-Analysis was then performed for the sensitivity and specificity of VELscope with a forest plot. Meta- Analysis on the efficacy of VELscope showed high sensitivity values (80.47%) in detecting oral lesions such as dysplasia, premalignant and malignant lesions. However, the study reported relatively low specificity rates (56.43%). The Forest plot graph also substantiated the results. The cumulative result of the meta-analysis on VELscope demonstrated that it is sensitive enough to detect mucosal abnormalities in the oral cavity but not consistent in discriminating dysplasia cases form non-dysplasia cases. Hence, it can be used only as an adjunct to other aids for screening of oral dysplasia.